2021
DOI: 10.1111/are.15456
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential reference genes by quantitative RT‐qPCR analysis of Takifugu rubripes under normal conditions and after Cryptocaryon irritans infection

Abstract: Quantitative real‐time PCR (RT‐qPCR) is more sensitive, specific, rapid and accurate than traditional semi‐quantitative and northern hybridization methods. It can more accurately analyse differences in gene expression and has become the most commonly used method for the determination of gene expression level. Up to now, few studies have focused on the stability of reference genes in Tetraodontidae. The purpose of this study was to use geNorm, BestKeeper and Normfinder software to select appropriate reference g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…GAPDH plays a vital role in glycolytic processes [41] and has also been shown to be unsuitable as a common reference gene in adipose tissue due to its differential expression levels in brown adipose tissue (BAT) and white adipose tissue (WAT) [42]. In addition to the above-mentioned classical internal reference genes, many studies have also found that RPL7 [43,44] and Rpl13α [45,46] can also be used as internal references. In the present study, 60SRP was the most stably expressed gene in freshwater drum adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH plays a vital role in glycolytic processes [41] and has also been shown to be unsuitable as a common reference gene in adipose tissue due to its differential expression levels in brown adipose tissue (BAT) and white adipose tissue (WAT) [42]. In addition to the above-mentioned classical internal reference genes, many studies have also found that RPL7 [43,44] and Rpl13α [45,46] can also be used as internal references. In the present study, 60SRP was the most stably expressed gene in freshwater drum adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2017) also reported 18S/ EF‐1α as stable RG in intestine of A. hydrophila infected group and 18S in PBS injected control group of Onychostoma Macrolepis . Liu et al (2021) reported EF‐1α and β‐actin as the most stable reference genes for muscle and gill in parasite infected tiger puffer fish. Information generated in this study can be used by research to study relative quantification of immune genes such as pathogen recognition receptor (PRR, i.e.…”
Section: Discussionmentioning
confidence: 99%